The Epimmunity Theory: The Single Cell Defenses against Infectious and Genetic Diseases - Barghouthi, Sameer A. (Frontiers in Immunology, 2017)
Single cell defense against diseases defines “epimmunity”. Epimmunity is complementary to the immune system and can neither be substituted by innate nor by acquired immunity. Epimmunity, the proposed new branch of immunity is further explored and analyzed for enucleated mature mammalian erythrocytes and nucleated erythrocytes of non-mammalian vertebrates leading to the development of ‘The Epimmunity Theory’. Enucleation of mammalian erythroblast and inactivation of nuclei in erythrocytes of non-mammalian vertebrates are major contributors to the collective immunity: epimmunity, innate, and acquired. The fact that diseases of mature erythrocytes are rare supports the notion that a single cell can resist microbial and genetic diseases; mature erythrocytes are refractory to malaria and cancer. Nucleated cells such as B-cells, T-cells, hepatocytes, and cell developmental stages are susceptible to genetic and specific microbial diseases depending on their nuclear activities and the receptors they express; such cells show lower epimmunity relative to mature erythrocytes. Epimmunity is important as a disease insulator that prevents the spread of diseases from an infected tissue to the majority of other tissues. Breakdown of epimmunity may lead to disease development. Key words: Erythrocytes, CD71 receptor, malaria, epimmunity theory, enucleation, RBCs, cancer, infection, extravasation, metastasis, immunity.